Unveiling family links after a sentence: a look at occupational therapy (Research, Society and Development, 2022)
In the past people suffering from some mental disorders were seen as subjects taken by evil forces. At another time, they were seen as insane and expunged from their own family, being isolated in their own homes. Over time, places were set up to allocate these persons, future psychiatric hospitals, and persons with mental disorders, who committed crimes, to confinement in Hospital of Custody and Psychiatric Treatment (HCTP), which in essence groups hospital characteristics and of prison. The general objective of this research was to understand the meaning of family for different social actors within HCTP. The specific objectives were to allow the expression of nine subjects through expressive activity on family; To understand the perception about the family of these inmates from the point of view of the reference team and to describe the professionals' perception of the work performed within the HCTP. For this, a qualitative methodology was used with a socio-historical theoretical-methodological basis, and for the data collection the open interview technique was used. The results make clear the importance of the profession in this environment for the maintenance of the occupational roles within the family context, providing the maintenance or the strengthening of the same ones, allowing a better adhesion of the inmates to the treatment within the HCTP, treatment that often can bring disbelief To the professionals, because of constant recidivism, of the own attitudes of the inmate, besides the difficulty of the continuity of the treatment when leaving the HCTP, due to the own network.